2021
DOI: 10.1177/13623613211060593
|View full text |Cite
|
Sign up to set email alerts
|

Social attention in anorexia nervosa and autism spectrum disorder: Role of social motivation

Abstract: Research suggests a relationship between anorexia nervosa and autism spectrum disorder. The aim of the current study was to examine social attention in anorexia nervosa and autism spectrum disorder compared with age- and sex-matched typically developing groups, and to examine whether lowered social motivation could explain reductions in social attention across the two disorders. Participants’ eye movements were tracked while watching a dynamic social scene. The proportion of fixation duration to faces, bodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 124 publications
1
4
0
Order By: Relevance
“…Findings from the pre-workshop questionnaire suggest that the patients attending the workshop were aware of their difficulties in social interactions, such as finding social situations difficult and having problems with eye contact, expressing emotions and engaging in social communication. This is in line with findings from experimental studies demonstrating that individuals with AN show significantly less eye contact than healthy controls (Harrison et al, 2018), they also spend less time watching social stimuli (Kerr-Gaffney et al, 2022). As expected, we found a large effect size difference in participant's self-reported ratings of the importance and their confidence in using eye contact, tone of voice, body language in the communication; suggesting that participants found all key elements of effective communication important but were not confident using this knowledge in real life situations.…”
Section: Discussionsupporting
confidence: 90%
“…Findings from the pre-workshop questionnaire suggest that the patients attending the workshop were aware of their difficulties in social interactions, such as finding social situations difficult and having problems with eye contact, expressing emotions and engaging in social communication. This is in line with findings from experimental studies demonstrating that individuals with AN show significantly less eye contact than healthy controls (Harrison et al, 2018), they also spend less time watching social stimuli (Kerr-Gaffney et al, 2022). As expected, we found a large effect size difference in participant's self-reported ratings of the importance and their confidence in using eye contact, tone of voice, body language in the communication; suggesting that participants found all key elements of effective communication important but were not confident using this knowledge in real life situations.…”
Section: Discussionsupporting
confidence: 90%
“…Through these mechanisms, the biases found in the present study could have an additional indirect negative effect on ED psychopathology. Of note, it has been suggested that different mechanisms may explain reduced attention to social cues in AN and autism spectrum disorders (Kerr-Gaffney et al, 2022). The present study might help to shed light on these different mechanisms as it indicates that increased attention to disorder-related characteristics of people (i.e., their bodies) might underlie the reduced attention to their faces in individuals with AN while probably other mechanisms (as for example attempts to reduce overstimulation or stress; Kerr-Gaffney et al, 2022) are responsible for the reduced attention to faces in individuals with autism spectrum disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, it has been suggested that different mechanisms may explain reduced attention to social cues in AN and autism spectrum disorders (Kerr-Gaffney et al, 2022). The present study might help to shed light on these different mechanisms as it indicates that increased attention to disorder-related characteristics of people (i.e., their bodies) might underlie the reduced attention to their faces in individuals with AN while probably other mechanisms (as for example attempts to reduce overstimulation or stress; Kerr-Gaffney et al, 2022) are responsible for the reduced attention to faces in individuals with autism spectrum disorders. However, in the present study pictures of faces were always presented alongside pictures of bodies (i.e., highly relevant disorder-related stimuli) so it remains unknown whether adolescents with AN would also look less at faces in the absence of disorder-related information (as found in adults with AN: Fujiwara et al, 2017;Kerr-Gaffney et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Response latency, time to first fixation and fixation duration are collected to assess attentional biases toward food cues. ▶ Two naturalistic scenes: Participants view a 124-s clip from the 1995-film ‘Welcome to the Dollhouse’ depicting a social situation of a young female attempting to find a table in a school cafeteria [ 71 ], followed by a 40-s clip of people being interviewed in the street [ 72 ]. During both videos, eye-tracking data will be collected to measure social attention and comprehension .…”
Section: Methodsmentioning
confidence: 99%